Fetal Noncompaction Cardiomyopathy and Histologic Diagnosis of Spongy Myocardium: Case Report and Review of the Literature - Luigi Nappi; Lorenzo Vasciaveo; Felice Sorrentino; Gennaro Scutiero; Piergiorgio Iannone; Pantaleo Greco (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Noncompaction cardiomyopathy (NCCM) and left ventricular noncompaction (LVNC), in their isolated form, are rare cardiomyopathies. They are characterized by a thickened myocardium due to the presence of deep trabeculae recesses, and to thick trabeculae. This condition is associated with a variable clinical phenotype including heart failure, thromboembolism, and sudden death. We report a case of LVNC at 26 weeks and 4 days of gestation revised on the basis of what is currently reported in the literature. A review of the literature was performed to better describe this rare condition. Left ventricular noncompaction is a rare fetal condition and it should be suspected in case of cardiomyopathy.